Estimating an Import Demand Function in Developing Countries : A Structural Econometric Approach with Applications to India and Sri Lanka - Emran, M. Shahe; Shilpi, Forhad (2012)
Owing to the unavailability of time-series data on the domestic market-clearing price of imports, the estimation of notional price and income elasticities of aggregate import demand remains a daunting task for a large number of developing countries. This paper develops a structural econometric model of a two-goods representative agent economy that incorporates a binding foreign exchange constraint at the administered prices of imports. A theoretically consistent parameterization of the "virtual relative price" of imports circumvents the data problem, and thus enables the estimation of income and price responses by cointegration approach. The price and income elasticity estimates for India and Sri Lanka, in contrast to the extant literature, have correct signs, high statistical significance, and plausible magnitudes.